Late Development of Metastatic Ovarian Mucinous Adenocarcinoma From Primary Gallblader Adenocarcinoma and High-grade Dysplasia. (January 2021) - Taylor, Jennifer; Shah, Rajeev; McElvanna, Kevin; Kelly, Paul J.; McCluggage, W. Glenn
Abstract : The ovary is a common site of metastatic mucinous adenocarcinoma. In most, but not all, cases the presence of a primary neoplasm elsewhere is already known and the metastasis is picked up at diagnosis or is discovered a relatively short time following the diagnosis of the primary neoplasm. We report 2 cases of metastatic gallbladder adenocarcinoma involving the ovaries of women aged 65 and 59 after long time periods of 8 and 5 yr following diagnosis of high-grade dysplasia or early adenocarcinoma of the gallbladder, respectively. In both cases, a review of the original operative notes suggested the possibility of intraoperative gallbladder rupture or bile leakage suggesting that the metastatic disease may have developed secondary to "seeding." In both cases, p53 immunohistochemistry revealed identical null mutation-type immunoreactivity within the gallbladder and ovarian neoplasms, assisting in confirming the ovarian disease as a metastasis from the gallbladder. The possibility of late ovarian metastasis of gallbladder dysplasia or adenocarcinoma secondary to rupture/bile leakage should be borne in mind.